Influence of Placental Cord Drainage in Management of the Third Stage of Labor: A Multicenter Randomized Controlled Study - Asıcıoglu, Osman; Unal, Canan; Asıcıoglu, Berhan Besımoglu; Temizkan, Osman; Yıldırım, Gokhan; Arıcı, Bulent; Gulova, Sıbel (American Journal of Perinatology, 2015)
Objective The aim of this study is to assess the effect of placental drainage during active management of the third stage of labor on reducing both blood loss and the length of the third stage.Study Design This prospective randomized controlled trial included 485 patients who underwent vaginal delivery in two tertiary hospital. Subjects were randomly allocated to the cord drainage group, in which the cord was unclamped after cutting (n = 242), or the control group, in which the cord was left clamped (n = 243). The primary outcome was mean blood loss during the third and fourth stages of labor.Results The mean estimated blood loss was significantly lower in the cord drainage group than in the control group (207.04 ± 123.3 vs. 277.63 ± 246.9 mL, respectively; p ˂ 0.001). The third stage of labor was significantly shorter in the cord drainage group than in the control group (3.5 ± 1.9 vs. 7.7 ± 3.4 minutes, respectively; p ˂ 0.001). No adverse events occurred during the cord drainage period.Conclusion Active management of the third stage of labor with the cord drainage method significantly reduced postpartum blood loss and the duration of the third stage.
Keywords: drainage; cord; stage; delivery